2021
DOI: 10.3389/fchem.2020.619832
|View full text |Cite
|
Sign up to set email alerts
|

Li7La3Zr2O12 Garnet Solid Polymer Electrolyte for Highly Stable All-Solid-State Batteries

Abstract: All-solid-state batteries have gained significant attention as promising candidates to replace liquid electrolytes in lithium-ion batteries for high safety, energy storage performance, and stability under elevated temperature conditions. However, the low ionic conductivity and unsuitability of lithium metal in solid polymer electrolytes is a critical problem. To resolve this, we used a cubic garnet oxide electrolyte (Li7La3Zr2O12 – LLZO) and ionic liquid in combination with a polymer electrolyte to produce a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…However, the interface resistance is still too high to promote Li-ion migration throughout the whole electrolyte. Hence, the Li solely migrates through PEO (Figure 1) (Chen et al, 2017;Zheng and Hu, 2018;Karthik and Murugan, 2019;Li et al, 2020b;Nguyen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the interface resistance is still too high to promote Li-ion migration throughout the whole electrolyte. Hence, the Li solely migrates through PEO (Figure 1) (Chen et al, 2017;Zheng and Hu, 2018;Karthik and Murugan, 2019;Li et al, 2020b;Nguyen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…82 By adding ceramic garnet-type solid electrolyte Li 7 La 3 Zr 2 O 12 (LLZO) particles combined with the [MPPYR][TFSI] IL, successful suppression of the lithium dendrites growth was achieved, resulting in high-performance batteries with good cyclability at different discharge rates. 79 Furthermore, the use of graphene oxide (GO) contributes to anion immobilization in the SPE, reducing the growth of lithium dendrites due to a more uniform distribution of the charges during the cycling process, as schematized in Fig. 8.…”
Section: State Of the Art Ionic Liquids For Battery Applicationsmentioning
confidence: 99%
“…Filler-added SPEs are flexible, more stable and have better interfacial compatibility with Li metal electrodes [141,151]. Furthermore, the SPEs possess better processability and higher ionic conductivity than the solid electrolytes [151,152]. Similar to inactive fillers, the size, concentration and morphology of active fillers impose different impact on the CSPEs.…”
Section: Composite Solid Polymer Electrolytesmentioning
confidence: 99%
“…In the work of Keller et al [155], LLZO-added CSPE containing PEO and LiTFSI did not contribute to ionic conductivity but exhibited improved electrolyte-electrode interfacial contact and higher electrochemical performance in lithium battery. It was found that the addition of LLZO in SPEs suppressed lithium dendrites growth [152][153][154][155][156]. The lithium and zirconium sites of LLZO can be doped with other elements to boost its properties.…”
Section: Composite Solid Polymer Electrolytesmentioning
confidence: 99%